Nasopharyngeal Carriage of Penicillin-Resistant Streptococcus pneumoniae among Children with Acute Respiratory Tract Infections in Thailand: a Molecular Epidemiological Survey - Dejsirilert, Surang (American Society for Microbiology, 1999)
The prevalence of penicillin-resistant Streptococcus pneumoniae in Thailand has dramatically increased over the last decade. During a national survey, which was conducted from 1992 to 1994, 37.2% of the pneumococci isolated from the nasopharynges of children with acute respiratory tract infections were penicillin resistant (MIC, ≥0.1 μg/ml). In order to investigate the prevalence and clonal relatedness of nasopharyngeal carriage of penicillin-resistant S. pneumoniae in Thailand, a molecular epidemiological survey was undertaken. To this end, 53 penicillin-resistant pneumococcal isolates from children who suffered from acute respiratory tract infections and who originated from five distinct regions of the country were characterized in detail. DNA fingerprint analysis demonstrated 13 clusters, i.e., genotypes shared by two or more strains, and 14 unique genotypes. The cluster size varied from 2 (nine clusters) to 11 strains (one cluster). Six of the 13 restriction fragment end labeling clusters consisted of two or more distinct serotypes, indicating frequent horizontal transfer of capsular genes. Geographical distribution of the genotypes among the five regions of Thailand demonstrated that only four genetic clusters were restricted to single areas of the country, whereas the other nine clusters represented isolates collected in two or more districts. These observations demonstrate that the majority of the genetic clusters are spread throughout the country. The most predominant genetic cluster, representing 21% of the isolates, was identical to the Spanish pandemic clone 23F. In addition, the second largest cluster matched the Spanish-French international clone 9V. These data indicate that the genetic clones 23F and 9V, which are widely spread throughout the world, are the most predominant multidrug-resistant pneumococcal clones in Thailand. Therefore, we conclude that these pandemic clones are primarily responsible for the increase in the prevalence of pneumococcal penicillin resistance in Thailand.